Reality and Illusion: Cervantes in Freud - Gómez, Carlos (Anales del Seminario de Historia de la Filosofía, 2007)
It is pretended to show the influence Cervantes had on Freud. Freud was worried about the psychic disorders. He was also disappointed by the methods of psychiatry had at that time. Freud was very interested in the plays of Cervantes, especially in El coloquio de los perros and El Quixote, where reality and illusion, and the relationship between sanity and insanity are their central axes. One of the possible readings of the great play is the one where limits between reason and unreason are not clear, to the point of achieving “the reason of the unreasonableness”, which would make it understandable and explicable. Real fantasy, fantastic reality, the demarcation between them was one of the topics that worried Freud. Freud is not a simple lawyer of the irrationality, but he also tries to find “the reason of the unreasonableness” that neurotics show in the symptoms he tried to explain in detail.